The layered structure of the clause in English and Arabic ditransitive verbs: A Role and Reference Grammar Perspective - Noori Hatem, Sara; al-Utbi, Mahdi I. Kareem (Technium Social Sciences Journal, 2022)
This paper presents the syntactic dimension of ditransitive verbs in terms of the universal theory of Role and Reference Grammar (RRG). This theory is syntactic in nature, but it also covers the semantic as well as the pragmatic aspects of any linguistic phenomenon. It assumes a universal framework through which syntactic constructions can be analyzed. However, the morphological structure that each language enjoys renders the universal treatment more complicated and can question the universal nature of such a theory. In this paper, an attempt is made to check if the universal tenet of the theory is maintained over two typologically different languages: English and Arabic in respect of the way that double-object constructions (DOCs) are represented in the theory. A limitation is made to answer these questions: does the rich morphological nature of Arabic affect the universality of RRG in so far as Layered Structure of the Clause (LSC) is concerned? and; where and how does the information about tense is represented in both languages? The results show that this theory is indeed universal when it deals with a syntactic phenomenon like DOCs and that a separate projection is dedicated to represent some related information about the clause and this is concluded from the analysis of the selected data.